2004
DOI: 10.1577/t03-057.1
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Native and Nonnative Fishes to Natural Flow Regime Mimicry in the San Juan River

Abstract: The maintenance or restoration of natural flow regimes has been proposed as one means of conserving native fishes. Native fish conservation is enhanced either through the restoration of natural fluvial geomorphic processes (and thus the maintenance of essential habitats) or by the suppression of nonnative fishes. The San Juan River of Colorado, New Mexico, and Utah was dammed in 1962 and its natural flow regime was lost. Beginning in 1993, the river was regulated to mimic a natural flow regime by increasing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
142
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 135 publications
(150 citation statements)
references
References 24 publications
8
142
0
Order By: Relevance
“…Studies elsewhere have found that red shiner abundance may dramatically increase during low-flow years and in river reaches directly below dains (Anderson et a]. 1983, Bonner and Wilde 2000, Propst and Gido 2004, similar to our observations. In contrast, drought and stable flows may negatively impact riverine species such as plains minnow and flathead chub (Cross andMoss 1987, Bonner andWilde 2000), which may explain their absence from our 2004 collections.…”
Section: Discussionsupporting
confidence: 92%
“…Studies elsewhere have found that red shiner abundance may dramatically increase during low-flow years and in river reaches directly below dains (Anderson et a]. 1983, Bonner and Wilde 2000, Propst and Gido 2004, similar to our observations. In contrast, drought and stable flows may negatively impact riverine species such as plains minnow and flathead chub (Cross andMoss 1987, Bonner andWilde 2000), which may explain their absence from our 2004 collections.…”
Section: Discussionsupporting
confidence: 92%
“…Although mimicking the natural flow regime may enhance native fish recruitment, it does not necessarily reduce non-native fish recruitment, particularly for highly fecund small-bodied nonnative fishes (Propst & Gido 2004). Therefore, identifying the mechanisms and specific aspects of flow that help maintain native river fishes may be needed to maintain these native populations.…”
Section: Limited Understanding Of Fish-flow Relationshipsmentioning
confidence: 99%
“…Large floods have been shown to be beneficial for the succession of fish species native to the Southwest (Rinne 2005;Propst and Gido (2004), and biota that have evolved under conditions of such variable discharge will return to a proper functioning condition following a flood. The magnitude and timing of a large flood are important to know because they affect the characteristics of the succession period that follows.…”
Section: Description Of Hydrologic Metric Determination and Flooding mentioning
confidence: 99%